The Cultural Meaning of Lexicons in “Ngusaba Bukakak” Ritual in Giri Emas Village - Kartika, Ni Made Intan Widya Surya; Budasi, I Gede; Swandana, I Wayan (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
One of the endangered traditions in Indonesia is the Ngusaba Bukakak ritual in Giri Emas Village, North Bali, which is a biennial agricultural ceremony dedicated to Dewi Sri, the goddess of fertility. Therefore, this study focuses on the identification, description, and interpretation of the lexicon used in the ritual to reveal its cultural meaning and contribution to Balinese identity. Data were collected through participant observation, in-depth interviews with ritual experts, and document analysis using a qualitative design framed by linguistic ethnography. Informants were selected using snowball sampling, which included the Traditional Village Head, Village Stakeholders, and Banten Serati, who had in-depth knowledge of ritual language. With triangulation ensuring data validity, the analysis followed Miles and Huberman's interactive model. The results of this study revealed that there are seventy lexicons spread across twelve stages of the ritual, including offerings, sacred objects, ritual actions, dances, and spiritual processions. These lexicons embody philosophical principles such as Tri Hita Karana which expresses harmony with God, society, and nature. This study concludes that the ritual lexicon functions as a linguistic element and as a cultural carrier that maintains Balinese identity, where its preservation is important for cultural sustainability, intergenerational transmission, and the protection of intangible heritage.